The gospel of germs : men, women, and the microbe in American life - Tomes, Nancy, 1952- (Harvard University Press, 1998)
Little more than a hundred years ago, ordinary Americans had no idea that many deadly ailments were the work of microorganisms, let alone that their own behavior spread such diseases. The Gospel of Germs shows how the revolutionary findings of late-nineteenth-century bacteriology made their way from the laboratory to the lavatory and kitchen, with public health reformers spreading the word and women taking up the battle on the domestic front. Drawing on a wealth of advice books, patent applications, advertisements, and oral histories, Tomes traces the new awareness of the microbe as it radiated outward from middle-class homes into the world of American business and crossed the lines of class, gender, ethnicity, and race.